Emerging Trends: Genomic Insights into the Virulence Factors of Bacterial Strains in Asymptomatic Bacteriuria during Pregnancy - Sharma , Medhavi (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Background: Urinary tract infections (UTIs) are a common problem in women at all stages of life, and assume greater importance particularly during pregnancy. UTIs can be divided into two types - lower tract infections and upper tract infections. Asymptomatic bacteriuria (ASB) is a common condition among pregnant women, characterized by the presence of a significant quantity of bacteria in the urine without the typical symptoms of a UTI. The primary objective of this study is to providing a genomic Insights into the Virulence Factors of Bacterial Strains in Asymptomatic Bacteriuria during Pregnancy. Pathogenesis, Epidemiology, Pathophysiology, Clinical Symptoms and Signs of ASB in Pregnancy have been discussed here. The diagnosis of ASB in pregnancy is typically made through urine culture. Prompt identification and treatment of ASB are crucial to mitigate adverse outcomes. Antibiotic therapy is the mainstay of treatment, and safe antibiotics include nitrofurantoin, cephalexin or amoxicillin, and cephalosporins. The study recommends that all pregnant women should be screened for ASB in early prenatal care and at the beginning of third trimester. In cases of increased risk of infection (e.g., diabetes mellitus), consider more frequent screening. Awareness among healthcare providers and pregnant women, coupled with appropriate interventions, can significantly improve perinatal outcomes in cases of ASB.